The song machine : inside the hit factory - Seabrook, John (W. W. Norton & Company, 2015)
There's a reason hit songs offer such guilty pleasure--they're designed that way. Over the last two decades a new type of hit song has emerged, one that is almost inescapably catchy. Pop songs have always had a "hook," but today's songs bristle with them: a hook every seven seconds is the rule. Painstakingly crafted to tweak the brain's delight in melody, rhythm, and repetition, these songs are highly processed products. Like snack-food engineers, modern songwriters have discovered the musical "bliss point." And just like junk food, the bliss point leaves you wanting more. In The Song Machine, longtime New Yorker staff writer John Seabrook tells the story of the massive cultural upheaval that produced these new, super-strength hits. Seabrook takes us into a strange and surprising world, full of unexpected and vivid characters, as he traces the growth of this new approach to hit-making from its obscure origins in early 1990s Sweden to its dominance of today's Billboard charts. Going beyond music to discuss money, business, marketing, and technology, The Song Machine explores what the new hits may be doing to our brains and listening habits, especially as services like Spotify and Apple Music use streaming data to gather music into new genres invented by algorithms based on listener behavior. Revelatory and original, this book will change the way you listen to music.--Adapted from book jacket.